Calcaneal Quantitative Ultrasound Indicates Reduced Bone Status Among Physically Active Adult Forager‐Horticulturalists. (March 2016) - Stieglitz, Jonathan; Madimenos, Felicia; Kaplan, Hillard; Gurven, Michael
ABSTRACT: Sedentary lifestyle contributes to osteoporosis and fragility fracture risks among modern humans, but whether such risks are prevalent in physically active preindustrial societies with lower life expectancies is unclear. Osteoporosis should be readily observable in preindustrial societies if it was regularly experienced over human history. In this study of 142 older adult Tsimane forager‐horticulturalists (mean age ± SD, 62.1 ± 8.6 years; range, 50 to 85 years; 51% female) we used calcaneal quantitative ultrasonography (qUS) to assess bone status, document prevalence of adults with reduced bone status, and identify factors (demographic, anthropometric, immunological, kinesthetic) associated with reduced bone status. Men (23%) are as likely as women (25%) to have reduced bone status, although age‐related decline in qUS parameters is attenuated for men. Adiposity and fat‐free mass positively co‐vary with qUS parameters for women but not men. Leukocyte count is inversely associated with qUS parameters controlling for potential confounders; leukocyte count is positively correlated within adults over time, and adults with persistently low counts have higher adjusted qUS parameters (6% to 8%) than adults with a high count. Reduced bone status characteristic of osteoporosis is common among active Tsimane with minimal exposure to osteoporosis risk factors found in industrialized societies, but with energetic constraints and high pathogen burden. © 2015 American Society for Bone and Mineral Research.